History, Present Status and Strategies of Rainbow Trout (Oncorhynchus mykiss) Farming in Jammu and Kashmir, India-A Review - Shah, Feroz A; Maqbool, Hafsa; Hafeez, Mehak; Bhat, Farooz A (Fishery Technology, 2023)
Jammu and Kashmir, particularly the Kashmir valley, contributes extensively to trout production in the Indian subcontinent. This cold-water fish species was successfully introduced into the region in the early 20th century from Europe. Eventually, trout fishery gained recognition within the Union Territory (UT) of Kashmir as a commercial and recreational venture. Being healthier and genetically superior to their counterparts from other Indian states, Kashmiri trout are in high demand, particularly for their eggs. Consequently, in 2021 alone almost 700,000 trout eggs have been transported to the North-Eastern states of India. Presence of trout in the waterbodies has made Kashmir one of the world’s major angling destinations. At present, the UT has 583 private and state-aided trout farms producing 650 tonnes of trout, making trout farming a sizable industry in the landlocked valley of Kashmir. Due to the unnatural conditions created by intensive rearing, farmed trout are more susceptible to disease agents than their wild counterparts, which is one of the main limitations to trout farming. After the initiation of cold water fish disease surveillance programme with the funding of the National Fisheries Development Board, more than 350 trout farmers had availed the facility for diagnosis and treatment of various fungal, bacterial, and parasitic infections. Besides fish health, there are many bottlenecks in the intensification and propagation of trout farming which have been discussed in detail in the paper.